Tracking structural phase transitions via single crystal x-ray diffraction at extreme conditions: advantages of extremely brilliant source. (8th February 2023) - Poręba, Tomasz; Comboni, Davide; Mezouar, Mohamed; Garbarino, Gaston; Hanfland, Michael
Abstract: Highly brilliant synchrotron source is indispensable to track pressure-induced phenomena in confined crystalline samples in megabar range. In this article, a number of experimental variables affecting the quality high-pressure single-crystal x-ray diffraction data is discussed. An overview of the recent advancements in x-ray diffraction techniques at extreme conditions, in the frame of European Synchrotron Radiation Facility (ESRF)- Extremely Bright Source (EBS), is presented. Particularly, ID15b and ID27 beamlines have profited from the source upgrade, allowing for measurements of a few-micron crystals in megabar range. In case of ID27, a whole new beamline has been devised, including installation of double-multilayer mirrors and double crystal monochromator and construction of custom-made experimental stations. Two case studies from ID27 and ID15b are presented. Hypervalent CsI3 crystals, studied up to 24 GPa, have shown a series of phase transitions: Pnma → P- 3 c 1 → Pm -3 n . First transition leads to formation of orthogonal linear iodine chains made of I3 - . Transformation to the cubic phase at around 21.7 GPa leads to equalization of interatomic I–I distances and formation of homoleptic In m- chains. The second study investigates elastic properties and structure of jadarite, which undergoes isosymmetric phase transition around 16.6 GPa. Despite a few-micron crystal size, twinning and dramatic loss of crystal quality, associated with pressure-induced phase transitions, crystal structures of both compounds have been determined in a straightforward matter, thanks to the recent developments within ESRF-EBS.